Giant DNA Viruses Infecting Unicellular Protists - Kyrychenko, A.M.; Burkot, V.M.; Shcherbatenko, I.S.; Кириченко, А.М.; Буркот, В.М.; Щербатенко, І.С. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Giant viruses (GV) are widespread in various ecosystems and ecological niches of the biosphere, most commonly in marine and freshwater aquatic ecosystems and soils. These viruses infect protists, a paraphyletic group of various unicellular, syncytial, and protozoan multicellular eukaryotes that are not true animals, plants, or fungus. The morphologically and functionally diverse group of protists includes parasites, commensals, or mutualistic symbionts of eukaryots, as well as heterotrophs, autotrophs, and mixotrophs. These giant viruses are currently classified into several families: Mimiviridae, Pithoviridae, Pandoraviridae, Phycodnaviridae, and the Mollivirus genus. GVs of unicellular protists belonging to the Mimiviridae family mainly infect the species of the Acanthamoeba genus. In this review, we provide the available information concerning giant viruses of the Mimiviridae family infecting other protists. These viruses include: Phaeocystis globosa virus PgV-16T (PgV), Aureococcus anophagefferens virus (AaV), Bodo saltans virus (BsV), Chrysochromulina ericina virus (CeV), and Phaeocystis pouchetii virus (PpV), which infect phytoplanktonic protists, as well as a giant virus of microzooplanktonic species, the Cafeteria roenbergensis virus (CroV). The review focuses on the major differences between these viruses and typical objects of current virology, their importance for understanding the evolutionary processes of genomes, genes, proteins, the biosynthetic and defense systems of organisms, as well as the important role of GV in regulating the aquatic microorganisms abundance and species diversity, carbon transfer and nutrient recycling in marine and freshwater reservoirs. Writing this review was motivated by the intention to inspire the interest of scientists in studying viruses as the most widespread biological creatures on Earth and ubiquitous symbiotic partners of all three domains of life.